In the Borderlands of Periodization with “The blythnes that hes bein”: The medieval / early modern boundary in Scottish history - Cowan, Mairi (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2012)
The conventional placement of the boundary between “medieval” and “early modern” periods in Scottish history has obscured our understanding of certain developments in fifteenth- and sixteenth-century Scotland. This paper proposes a reconsideration of periodization so that the fifteenth and sixteenth centuries be examined against the backdrop of early modern (rather than medieval) historical scholarship, and not only in the context of Europe but also in the more expansive field of Atlantic history. With such a shift in periodical alignment, several features become more apparent including a change to religious culture in connection with the Catholic Reformation, an increase in social discipline that helped shape the Protestant Reformation, and early participation in the Atlantic slave trade.